MERAWAT SENTIMEN ANTI JOKOWI (STUDI KASUS: PILKADA JAWA BARAT 2018) - Raden Muhammad iqbal; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2020)
General elections are a product of the democratic system. Indonesia has several general elections, from the smallest (village) level to the presidential election. The journey of a heterogeneous democratic country has many problems, especially since many ethnic groups, races, and religions in Indonesia are involved in politics. Although ideally, identity politics is not good enough in the course of a democratic country, until now the issue of identity politics is still widely used. One of them is an expression of identity politics in West Java which was used by the Sudrajat and Ahmad Syaikhu pairs in the 2018 West Java Pilkada with the use of the hashtag # 2019GantiPresiden. Therefore, this study aims to determine and analyze what factors make identity politics and other entities used during the 2018 West Java regional elections, so that things that are not predicted will happen in the real world.This research method uses the Mix Method research method, where quantitative research is the main method. Qualitative research is a supporting method. Quantitative data were obtained from 96 respondents in West Java, especially in Bogor, Sukabumi, Bekasi, and Bandung Regencies. Qualitative data were obtained from 2 sources from the Gerinda Party and PKS.The results show that West Java culture is still very thick with its religious atmosphere, in which Islam is the majority religion of voters and is the reason for choosing candidates for the 2018 West Java gubernatorial running mate. In addition to having an impact on the results of the 2018 West Java regional election, West Java society is also polarized by an identity group voicing the hashtag # 2019ChangePresident and able to shape the behavior of the people (voters) in making choices in the 2019 elections. Then the impact of identity politics in West Java, many West Javanese people identify Jokowi with China. Judging from Jokowi's policies and political attitudes and the # 2019GantiPresiden hashtag which was able to arouse and hold back anti-Jokowi sentiment in West Java. The Prabowo and Sandiaga Uno pair dominate and nearly win votes in every district in West Java.